Efficacy of contrast‐enhanced ultrasound in detection of type II endoleak after abdominal aortic aneurysm surgery: A prospective cohort study. Issue 4 (2nd March 2022) - Zhao, Xiaoning; Liu, Yong; Sun, Mingyan; Wang, Yingying
Abstract: Purpose: This study aimed to evaluate the efficacy of conventional contrast‐enhanced ultrasound (CEUS) in detection of type II endoleak after endovascular abdominal aortic aneurysm repair (EVAR). Methods: From January 2015 to April 2018, 205 patients underwent EVAR were included. CEUS and computed tomography angiography (CTA) were performed at 1‐month follow‐up postoperatively to detect type II endoleak. CEUS was performed at 3‐ and 6‐month follow‐up to evaluate the development of type II endoleak. The diameter extension of type II endoleak increased greater than 5 mm was defined as enlarge group, and that increased less than 5 mm was defined as stable group. The difference of arrival time (AT) of contrast agent, maximum cross‐sectional area (MCSA) of contrast agent and the blood flow velocity (BFV) of the abnormal blood around the stent graft were compared. Results: At 1‐month after EVAR, 65 cases of endoleak were detected by CEUS, including 25 cases of type I, 30 cases of type II endoleak and 10 cases of type III endoleak. Among them, 50 cases were also detected by CTA. The diameter extension of 12 cases of type II endoleak increased greater than 5 mm, and that of eight cases increased less than 5 mm. The average AT of the enlarge group was significantly shorter than that of the stable group, while the MCSA of contrast agent and the BFV were significantly higher than that of the stable group ( p < 0.05). Conclusion: CEUS has predictive value for the natural outcome of type II endoleak. Abstract : This study evaluated the efficacy of conventional contrast‐enhanced ultrasound (CEUS) in detection of type II endoleak after endovascular abdominal aortic aneurysm repair (EVAR). Total 205 patients underwent EVAR were performed CEUS and computed tomography angiography at 1‐month postoperatively to identify type II endoleak. CEUS was performed at 3‐ and 6‐month follow‐up to evaluate the development of type II endoleak. The average arrival time of the enlarge group (diameter extension increased greater than 5 mm) was significantly shorter than that of the stable group (diameter extension increased less than 5 mm), while the maximum cross‐sectional area of contrast agent and the blood flow velocity were significantly higher than that of the stable group. CEUS has predictive value for the natural outcome of type II endoleak.